Effects of blue-light irradiation during dental treatment - Fumihiko Yoshino; Ayaka Yoshida (Elsevier, 2018)
Summary: In dentistry, blue light is widely used for tooth bleaching and restoration procedures involving composite resin. In addition, many dentists use magnification loupes to enable them to provide more accurate dental treatment. Therefore, the use of light is indispensable in dental treatment. However, light can cause various toxicities, and thermal injuries caused by light irradiation are regarded as particularly important. In recent years, the eye damage and non-thermal injuries caused by blue light, the so-called "blue light hazard", have gained attention. Unfortunately, much of the research in this field has just begun, but our recent findings demonstrated that blue-light irradiation generates reactive oxygen species (ROS) and induces oxidative stress in oral tissue. However, they also showed that such oxidative stress is inhibited by antioxidants. There have not been any reports that suggested that the ROS-induced phototoxicity associated with blue-light irradiation causes direct clinical damage, but some disorders are caused by the accumulation of ROS. Therefore, it is presumed that it is necessary to suppress the accumulation of oxidative stressors in oral tissues during treatment. In the future, we have to promote discussion about the suppression of phototoxicity in dentistry, including concerning the use of antioxidants to protect against phototoxic damage. Keywords: Blue light, Heat damage, Reactive oxygen species and free radicals, Oxidative stress, Antioxidant